ONLINE MARKETING MIX AND ONLINE BUSINESS QUALITY AFFECTING CUSTOMER’S SATISFACTION: A CASE OF ASIAPAC NET MEDIA LIMITED, CHINA - Fei, Liu; Kenikasahmanworakhun, Phatthararuethai (วารสารการจัดการโซ่คุณค่าและกลยุทธ์ธุรกิจ, 2023)
Customer satisfaction is directly tied to a company’s capacity to attract and retain customers, hence businesses must understand the relationship between their online marketing strategy, online business quality, and customer satisfaction. This research has the objectives: 1) to study the personal factors that affect customer satisfaction in Asiapac Net Media Limited China, 2) to study the online marketing mix that correlates with customer satisfaction in Asiapac Net Media Limited China, and 3) to study online business quality that correlates with customer satisfaction in Asiapac Net Media Limited China. This research is quantitative. Convenience sampling was used to select 400 Asiapac Net Media Limited clients in the People’s Republic of China. Data was examined using frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, and multiple regression. This study reports: 1) Several personal factors, such as age and level of education, affect the customers’ satisfaction with Asiapac Net Media Limited China at a statistically significant level of 0.05. 2) Online marketing mix variables such as experience, everywhere, exchange, and evangelism had a positive correlation with consumers’ satisfaction with the use of Asiapac Net Media Limited China’s services at a statistically significant level of 0.05 and predictive power of 37.8 percent. And 3) online business qualities such as information quality, service quality, and system quality were positively correlated with customers’ satisfaction with the use of Asiapac Net Media Ltd China’s services at a statistically significant level of 0.05 with a prediction power of 42.0%.